NILAI MAGIS DALAM NOVEL SUNYARURI KARYA RISA SARASWATI TEORI REALISME MAGIS: MAGICAL VALUE IN THE NOVEL SUNYARURI BY RISA SARASWATI MAGICAL REALISM THEORY - Lotong, Yana; Nensilianti; Abidin, Aslan (Journal of Applied Linguistics and Literature, 2024)
This research aims to describe the magical value contained in the novel Sunyaruri by Risa Saraswati. This research uses descriptive qualitative method by describing the data obtained based on the theoretical studies used. The data used in this research are texts that describe the magical value in the novel Sunyaruri by Risa Saraswati using magical realism studies. The results show that there are four magical values that describe magical values in each quote in the novel, namely magical values based on place, magical values based on spirits, magical values based on objects and magical values based on sound